The genus Ipomoea (Convolvulaceae) in the Mata da Pimenteira State Park, semiarid region of Brazil - Costa,Rosemeire Santos (2021)
Abstract The Mata da Pimenteira State Park (MPSP) is an important remnant of caatinga vegetation in the semiarid region of Pernambuco state, Brazil. The park holds great biodiversity, but relatively few taxonomic studies have been undertaken in the area. We present a taxonomic study of Ipomoea in the MPSP based on field observations and collections deposited in the Herbarium of the Semiarid of Brazil - UAST / UFRPE (HESBRA). The species were identified based on the specialized literature, comparisons with type images available online, and protologues. Fourteen species of Ipomoea were identified - more than three times the previously known number. Two Ipomoea species recorded in the MPSP are endemic to Brazil (I. bahiensis and I. brasiliana), three others are exclusive to the Caatinga domain (I. marcellia, I. rosea, and I. tenera), and the remaining are widely distributed in South America. The habit, type and shape of leaf blade and sepals, corolla size and shapes, and presence or absence of subapical rostrum on the external sepals were the most relevant distinctive characteristics. An identification key, descriptions, comments on distribution and diagnostic characteristics, and phenological data of the species are presented.